TANTANGAN IMPLEMENTASI SIMRS DARI PERSPEKTIF TENAGA KESEHATAN: STUDI KUALITATIF DI RUMAH SAKIT DAERAH [CHALLENGES OF SIMRS IMPLEMENTATION FROM THE PERSPECTIVE OF HEALTH PERSONNEL: A QUALITATIVE STUDY IN A REGIONAL HOSPITAL] - Yuana Cita; Ade Miranda; Mona Fandani; Sandi Mahputra; Irvincha Aura Fasya Irawan; Vip Paramarta (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
The digitalization of health information systems has become a vital component in healthcare service reform in many countries, including Indonesia. One concrete form of this transformation is the implementation of the Hospital Management Information System (SIMRS), which aims to integrate all administrative, management, and clinical service processes electronically. The implementation of SIMRS is considered a strategic step in improving efficiency, service quality, and accountability in hospital data management (Ministry of Health of the Republic of Indonesia, 2020). However, in reality, regional hospitals face more complex challenges compared to central or private hospitals. These challenges include limited budget allocation for IT infrastructure, a lack of reliable IT personnel, and unequal access to stable internet networks (Putri & Harjo, 2022). These various obstacles not only hinder the effective implementation of SIMRS but also potentially degrade the quality of patient care if the system does not function optimally. This study aims to explore in depth the perspectives of healthcare workers on the challenges of SIMRS implementation in regional hospitals. Using a qualitative descriptive approach, the study analyzes the experiences, perceptions, and obstacles faced by hospital staff in the daily use of SIMRS. The research object is a Regional Public Hospital (RSUD), with research subjects consisting of hospital staff directly involved in the SIMRS implementation process. Data collection techniques included observation and interviews. The findings conclude that the main challenges in SIMRS implementation in regional hospitals include user competence, infrastructure support, and organizational readiness. Many healthcare workers are not yet technically or mentally prepared due to limited training, additional workloads, and systems that do not meet the needs of specific work units (Wibowo et al., 2022). Equipment limitations, unstable internet connections, and dependence on technicians worsen the situation. Data security issues are also a concern, as SIMRS stores sensitive medical information (Setiawan & Nugroho, 2021). System disruptions that force manual work reduce efficiency and increase the risk of errors. Therefore, ongoing practical training, infrastructure modernization, more user-friendly systems, and involving healthcare workers in evaluations are necessary to ensure SIMRS can be implemented optimally and contextually (Rahmawati et al., 2023).